As facetas da crônica do século XIX e suas expressões na Gazeta da Parahyba - Silva, Otoniel Machado da (2017)
This work investigated the nineteenth century chronicle in the ambit of the Gazeta da Parahyba, newspaper that circulated in the soil of Paraíba between 1888 and 1890. Based on the gaps, but comprehending the social place (CERTEAU, 1982 [1975]), of the literary criticism and historiography, that did not foresee the gender chronicle in the nineteenth century of Paraiba, the research took as a basis the available primary sources in the sites of the Hemeroteca of the National Library and of the Project Journal and Literary feuilletons of the Paraíba in the 19th century, idealized by Socorro Barbosa (2007). The study is based methodologically on the premises of the Cultural History (BURKE, 2008;2010), following the trails and the paths pointed by Michel de Certeau (2009) and Roger Chartier (1999) in the importance given to the practices of reading and to the materiality of the texts. Besides this, the work greets all the direction established by Marlyse Meyer (1996;1998) and her studies about the chronicle and the feuilletons, as it is debtor of the proposals launched by Socorro Barbosa (2007;2011). Some questions were motivational to the development of the research, among them: was there chronicle in Paraiba on the 19th century? How did it configure? What does the literary historiography from Paraíba says about the chronicle of the nineteenth century? Was there any deletion, why? Is it possible to fulfill the supposed historic gaps? Answering these inquiries onwards primary sources – Paraiba newspapers of the 19th century -, a classification for the chronicle writings of the nineteenth century was proposed. And, starting with the Gazeta da Parahyba, a rich production of chronicles was proved, contributing with new data for the history of the literature of Paraíba/Brazil. The Brazilian literary criticism and historiography on the gender chronicle was reviewed since the pioneer critics, such as Silvio Romero (1888) and José Veríssimo (1904, 1907, 1915), going through the traditional criticism, exemplified by Afrânio Coutinho (2003), Massaud Moisés (2007) and Antonio Candido (1992), until we reach the most recent studies of Marlyse Meyer (1996), Marcus Soares (2014), Chalhoub, Neves and Pereira (2005). In the ambit of the literary historiography of Paraiba, above all the considerations of João Lelis de Luna Freire (1953) and Hildeberto Barbosa Filho were analyzed, (1985; 1996; 1999; 2001; 2003; 2005). On the history of the press in Paraíba, this thesis is a debtor of the studies of Eugenio Toscano de Brito (1910 [1897]), founder and editor in chief of the Gazeta da Parahyba, Alcides Bezerra (1922 [1920]), José Leal (1960), Eduardo Martins (1976; 1978) and Fátima Araújo (1983; 1986 [1985]), Besides the own chronistic writings of the Gazeta, in the fountain pen of its other editors. The results of the thesis include the presentation of a group of chroniclers that can be numbered among the pioneers of the chronicle in the nineteenth century of Paraíba: Eugenio Toscano de Brito, Arthur Achilles, Eduardo Marcos de Araújo, Antonio da Cruz Cordeiro Junior and Alexandre de Faria Godinho, besides those which pseudonym was not possible to find out.